PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN PT. TELKOM PAREPARE - Novita, Dien (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the effect of competence and work discipline on the work performance of PT Telkom Parepare employees. The object of this research is the employees of PT Telkom Parepare City. To obtain data to support this research, the researcher used a questionnaire method with a sample size of 50 employees. The data analysis tool used in this research is a study with multiple linear regression models. Based on the results of the research that has been done, it shows that: 1) Competence has a significant effect on the work performance of PT Telkom Parepare employees. 2) Work discipline has a significant effect on the work performance of PT Telkom Parepare employees.